2013
DOI: 10.1055/s-0032-1333483
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte Donation and Endometriosis: What Are the Lessons?

Abstract: Endometriosis affects 6 to 10% of reproductive-age women. 1 The prevalence of this condition in women experiencing pain, infertility, or both is as high as 35 to 50%. 2 The monthly fecundity rate in couples diagnosed with both endometriosis and infertility is between 2% and 10% per month, 3 whereas it is 25 to 30% for normal couples of reproductive age for the first three cycles. It declines to 4% when couples have been trying to conceive for >1 year. 4 Even minimal endometriosis may be associated with marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 42 publications
(45 reference statements)
2
29
0
4
Order By: Relevance
“…Consequently, we chose to use a 10 % dilution of PF for this study. We observed a significant decrease in blastocyst development from 63.6 to 38.9 % with the addition of 10 % PF-E, confirming the embryotoxic impact of endometriotic peritoneal fluid [27]. The addition of 10 % PF-NL to the embryo culture media did not result in a significant decrease in the BDR.…”
Section: Discussionsupporting
confidence: 60%
“…Consequently, we chose to use a 10 % dilution of PF for this study. We observed a significant decrease in blastocyst development from 63.6 to 38.9 % with the addition of 10 % PF-E, confirming the embryotoxic impact of endometriotic peritoneal fluid [27]. The addition of 10 % PF-NL to the embryo culture media did not result in a significant decrease in the BDR.…”
Section: Discussionsupporting
confidence: 60%
“…Any problem in these systems, such as endometriosis-induced inflammation, impairs reproductive function [18]. Endometriosis characteristically causes chronic intraperitoneal inflammation and may cause infertility by several pathways, including disturbed folliculogenesis, reduced oocyte quality, impaired embryo development, and reduced endometrial receptivity [19, 20]. Inflammatory factors, such as TNF-α, are higher in the peritoneal and follicular fluid of infertile women with endometriosis compared with normal women [21].…”
Section: Discussionmentioning
confidence: 99%
“…Oocyte donation studies might be able to determine whether oocyte quality or endometrial receptivity is more important for endometriosis-induced infertility. Reviews on oocyte donation have shown a higher rate of implantation problems and a lower pregnancy rate in patients receiving oocytes from donors with endometriosis, while outcomes are not affected by the status of the recipient [20]. These data suggest that infertility in women with endometriosis may be the result of poor oocyte quality due to an increase in inflammatory factors rather than endometrial issues [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggestion is in line with studies from oocyte donation programmes. Implantation rates were reduced with oocytes from women with endometriosis transferred to women without endometriosis, whereas embryos from healthy donors, transferred to women with endometriosis, did not affect implantation rates [12].…”
Section: Introductionmentioning
confidence: 87%